2022
DOI: 10.26710/jbsee.v8i2.2339
|View full text |Cite
|
Sign up to set email alerts
|

Post Covid-19 Pandemic Experience of Architecture Students in Mehran University of Engineering and Technology Jamshoro Sindh Pakistan

Abstract: Purpose: This paper deals with the educational experience of the students of the architecture department at Mehran University of engineering and technology, Jamshoro, Sindh, Pakistan during the peak covid-19 pandemic when everyone was working remotely from their homes, etc. This paper shows that when there was the first peak COvid-19 wave from mid-march to August 2020, how do students die with the sudden change in learning patterns from physical classes to online classes? Methodology: A questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The shift to online classes has posed specific challenges for AE, primarily due to its reliance on the social studio setting, which has been a significant challenge in the new normal of online education [63]. Furthermore, experiences from specific institutions, such as the Mehran University of Engineering and Technology in Pakistan, have shown that while theoretical classes can be effectively taught online, practical/studio work in architecture is more challenging to deliver in an online format [64].…”
Section: Research Background and The Literature Gapmentioning
confidence: 99%
“…The shift to online classes has posed specific challenges for AE, primarily due to its reliance on the social studio setting, which has been a significant challenge in the new normal of online education [63]. Furthermore, experiences from specific institutions, such as the Mehran University of Engineering and Technology in Pakistan, have shown that while theoretical classes can be effectively taught online, practical/studio work in architecture is more challenging to deliver in an online format [64].…”
Section: Research Background and The Literature Gapmentioning
confidence: 99%